Studi Aplikasi Vacuum Preloading Sebagai Metode Alternatif Percepatan Proses Konsolidasi pada Tanah Lempung Lunak Jenuh Air: Trial GVS pada Perumahan Pantai Indah Kapuk, Jakarta - Suhendra, Andryan; Irsyam, Masyhur (Bina Nusantara University, 2011)
Vacuum preloading is an alternative method to improve water-saturated soft clay by accelerating the consolidation process. A trial using GVS system was done at Pantai Indah Kapuk residence, Jakarta to investigate the system reliability. Monitoring equipments used include settlement plate to measure the consolidation decrease, piezometer to measure pore water tension, inklinometer to identify the soil direction and lateral movement during the vacuum preloading process, and manometer to measure the vacuum pump pressure. Analytical calculations to estimate the consolidation decrease is done using one-dimensional consolidation theory of Terzaghi. Besides, a numerical analysis is performed by element method up to Plaxis software application. Meanwhile, the monitoring results are achieved using Asaoka theory that estimates the achieved degree of reduction and consolidation. The monitoring results and theoretical analysis indicate that the GVS system included in the vacuum preloading method is quite reliable as an alternative method of consolidation acceleration of water-saturated soft clay.